Design and development of hybrid solar dryer for flowers - PACHPINDE, PADMAPANI; SHARMA, P K; MANI, INDRA; PARRAY, ROUF A; NAMITA, NAMITA (The Indian Journal of Agricultural Sciences, 2019)
A hybrid solar dryer was developed consisting of three shelves of 0.55 m2 area each in the drying chamber. This dryer works on the principal of solar thermal and solar photovoltaic system. The performance evaluation was done with rose and marigold flowers. It was found that both flowers when dried at 45Â°C were significantly (P